A framework for addressing the challenges of business process change during enterprise systems integration. Issue 2 (18th November 2019) - Javidroozi, Vahid; Shah, Hanifa; Feldman, Gerald
Abstract : Purpose: Enterprise systems integration (ESI) is necessary for today's business environment to access real-time data and quickly respond to fluctuating market demand. business process change (BPC) as a significant prerequisite of ESI encompasses various challenges that must be tackled by employing success factors, techniques and approaches. The purpose of this paper is to focus on BPC challenges and develop a conceptual framework for addressing BPC challenges in ESI. Design/methodology/approach: BPC challenges and their success factors were first identified through a literature analysis. Then, the findings from the literature were thematically analysed and qualitatively validated through 35 unstructured interviews for developing the conceptual framework. Findings: The findings from the literature suggested 17 BPC challenge along with their success factors. During the validation process, 15 BPC challenges were accepted by all interviewees, while most of the respondents disagreed with the two challenges of "consolidation of information system re-engineering with BPR", and "customization". Moreover, "risk" was suggested as a BPC challenge by several interviewees. Thus, the study offered a modified list of BPC challenges, which was empirically validated. Originality/value: The study proposes a conceptual framework for addressing BPC challenges in ESI that enables enterprises to design their systems integration roadmap, based on an understanding of BPC challenges and their success factors, as well as supporting solution providers to develop solutions for effective and efficient BPC. Furthermore, the framework will act as a basis for BPC and developing a similar framework for other related contexts, such as smart cities.